Reits' Growth Options and Asset Pricing Dynamics across Time - Cheng Wee Tan; Dogan Tirtiroglu; Ercan Tirtiroglu (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
Our paper makes two empirical contributions on REITs' asset pricing over three sequential and mutually exclusive time periods. The first yields the beta estimates of (i) assets, (ii) growth options and (iii) assets-in-place, embedded in the valuations of REITs. We develop a new approach to estimate the latter two betas and, to our knowledge, provide the first-ever REIT evidence on them. The second investigates the evolving roles, from a capital markets viewpoint, of the four pricing factors of the Carhart model on REITs' portfolio returns. In each investigation, we clean out, when needed, the unprecedented and overwhelming effects of GFC and the Eurozone bailout crisis. Our main results show that (i) the betas of growth options are larger than those of assets-in-place, raising a question mark about the 'income stock' description of REITs, (ii) the estimates of the equity beta for REITs are always positive and very highly significant, not consistent with the reports of the 'death of beta' from the mainstream finance literature, (iii) the capital markets' one-year momentum measure does not affect REITs' portfolio returns, and (iv) REITs exhibit a lot of progress in integration into the capital markets.
Keywords: G10; G11; G12; 330; asset pricing; growth option; momentum; REITs; GFC